Promoting botanical literacy with a mobile application - CampusFlora - using an interdisciplinary, student-as-partners approach - Dimon, Richard; Pettit, Lachlan; Cheung, Caroline; Quinnell, Rosanne (International Journal for Students as Partners, 2019)
In this article, we describe our students-as-partners process for bringing undergraduate and academic staff together to develop a mobile application (app) - CampusFlora - for use across our campuses. Our project at the University of Sydney, Australia, was conceived as a way to improve the botanical literacy of biology students by engaging undergraduates to develop online maps of plant locations coupled with information relevant to biology curriculum. Through continuous improvements to the CampusFlora app system, we have expanded the user-base well beyond the life science student cohorts and now offer content that embraces cultural competence and organisational health initiatives. We offer reflections from student and staff partners on the project that highlight the value of the students-as-partners approach, and the potential value of establishing student partnerships across disciplines, across institutions, and into the community at large.